Evaluating Population and Environmental Education through Ecovocation: Critical Urbanization Literacy, Socio-Ecological Vulnerability, and Rights-Based Learning in Jakarta - Syaifudin, Syaifudin; Purwanto, Agung; Budiaman, Budiaman (LPPM Universitas Negeri Jakarta, 2026)
This article re-organizes empirical data on migrant women’s vulnerability in Jakarta’s SPA industry into the scope of educational evaluation. Rather than treating Population and Environmental Education (PEE) only as demographic and ecological literacy, the study evaluates PEE as a rights-based educational praxis capable of interpreting, preventing, and responding to structural vulnerability. Using a critical qualitative educational-evaluation design, the study examines data generated through semi-structured interviews, limited participant observation, and document analysis involving SPA workers, community actors, NGO and legal-aid advocates, academics, and public officials. The analysis applies four evaluative criteria: relevance, responsiveness, inclusiveness, and transformative utility. The findings indicate that PEE is highly relevant when it is reconstructed as critical urbanization literacy that prepares migrants to understand labor-market exclusion, safe migration, rights, and urban citizenship. It is responsive when environmental education moves beyond behavioral campaigns and evaluates socio-ecological vulnerability, including dense housing, sanitation problems, pollution, flooding, and unequal access to healthy urban space. It becomes inclusive when the voices of stigmatized informal workers are treated as legitimate evidence for educational planning and social protection. Finally, the study proposes ecovocation as a transformative evaluation model that integrates critical consciousness, environmental justice literacy, legal and labor-rights education, safe reporting mechanisms, and non-stigmatizing vocational pathways. The article contributes to educational evaluation by demonstrating how qualitative evidence can be organized into a defensible, triangulated, and utilization-oriented framework for evaluating PEE in contexts of urban inequality.